Geo-Congress 2014 Technical Papers 2014
DOI: 10.1061/9780784413272.133
|View full text |Cite
|
Sign up to set email alerts
|

Matric Suction in Recycled Unbound Granular Materials

Abstract: The matric suction within unbound granular materials (UGMs) can be small when compared with cohesive soil, however suction can influence the engineering behavior of UGMs. Unfortunately, there are few studies on the potential matric suction in UGMs. This paper presents matric suctions for seven recycled products and one virgin aggregate. The products were recycled concrete aggregate (RCA) and recycled clay masonry blended with RCA. The percentage of masonry in the blended materials varied between 10% and 30% by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…They observed that water content had little impact on the resilient modulus of base materials compared to the subgrade soils. Studies conducted by [23,24,17], found that the matric suction has been appeared to be a vastly improved predictor of engineering behavior than moisture content.…”
Section: Moisture Content and Matric Suctionmentioning
confidence: 99%
See 1 more Smart Citation
“…They observed that water content had little impact on the resilient modulus of base materials compared to the subgrade soils. Studies conducted by [23,24,17], found that the matric suction has been appeared to be a vastly improved predictor of engineering behavior than moisture content.…”
Section: Moisture Content and Matric Suctionmentioning
confidence: 99%
“…Numerous studies stated that the Mr of UGMs and subgrade soils fundamentally depends on moisture content or matric suction in both laboratory and in-situ condition [14,17].…”
Section: Moisture Content and Matric Suctionmentioning
confidence: 99%